IMMU-05. THE INFLUENCE OF THE KETOGENIC DIET ON THE IMMUNE TOLERANT MICROENVIRONMENT IN GLIOBLASTOMA. (14th November 2022) - Kesarwani, Pravin; Zhao, Yi; Kant, Shiva; Miller, C Ryan; Chinnaiyan, Prakash
Abstract: Glioblastoma (GBM) represents a particularly aggressive and immune-resistant cancer. Preclinical investigations have identified the anti-tumor activity of a ketogenic diet (KD) in GBM, potentially being used as a tool to target its glycolytic phenotype. Since immune cells in the tumor have a similar reliance upon nutrients to perform their individual functions, we sought to determine if the KD influenced the immune landscape of GBM. Utilizing genetically-engineered murine GBM tumor cells orthotopically implanted in immune-competent mice, we demonstrate that KD improved survival in GBM. Immunophenotyping of tumors identified a novel role KD plays in macrophage polarization, with a paradoxical 50% increase in immune-suppressive M2-macrophages and a decrease in pro-inflammatory M1-macrophages. We recapitulated KD in vitro using a modified cell culture based on comprehensive metabolomic profiling of serum in KD-fed mice. Consistent with in vivo studies, murine macrophages cultured in these conditions skewed polarization towards the M2-phenotype with immune-suppressive properties. We went on to mechanistically link these findings to the activation of transcription factor PPARg. Although anti-tumor activity was observed in mice fed a KD, we hypothesized this parallel increase in M2 macrophage polarization tempered its potential therapeutic benefit. Colony-stimulating factor 1 (CSF-1) plays a central role in macrophage differentiation, and CSF-1R inhibition is actively being investigated as a strategy to skew their polarization towards an M1-phenotype. Therefore, we tested a combination of KD with the brain-penetrant CSF-1R inhibitor BLZ945. Consistent with our hypothesis, this combination demonstrated a striking improvement in survival (p = 0.0004), with 50% of mice achieving long-term survival ( > 50 days). Correlative studies confirmed the capacity of BLZ945 to normalize KD-induced increases in M2s, and the combination induced an increase of anti-tumor iNOS+M1s. Combinatorial strategies using agents designed to modulate macrophage polarization represent a rational approach to improve the anti-tumor activity of KD in GBM.